1999
DOI: 10.1046/j.1524-4725.1999.99064.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefits of Lightweight Compression: Reduction of Venous-Related Symptoms by Ready-to-Wear Lightweight Gradient Compression Hosiery

Abstract: Use of lightweight (low compression) RTW gradient compression hosiery is very effective in improving symptoms of discomfort (P < 0.01), swelling (almost P < 0. 05), fatigue (P < 0.05), aching (P < 0.01), as well as leg tightness. Improvement of symptoms is statistically significant compared to no compression when hosiery was worn regularly during waking hours for 4 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 15 publications
0
33
0
2
Order By: Relevance
“…Other studies have reported beneficial effects of low-grade compression stockings on subjective complaints [12, 14, 15, 16]and venous haemodynamics [8, 15, 16, 17, 18]as well.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported beneficial effects of low-grade compression stockings on subjective complaints [12, 14, 15, 16]and venous haemodynamics [8, 15, 16, 17, 18]as well.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Immobilisation, and prolonged standing and sitting, which can raise venous pressure and lead to incompetence of the valves in the long veins, have been suggested to be the principal aetiological factors in the pathogenesis of such venous disorders. [3][4][5][6][7][8] By providing a controlled external pressure gradient from the ankle to the thigh, with the greatest pressure at the ankle and the least pressure at the thigh, GCS can reduce the increased hydrostatic pressure and redress the pressure balance between the deep and superficial veins, thus helping improve venous circulation in the lower extremities. 9,10 Pressure levels and gradient distribution are the two critical parameters in the compression performance of GCS products.…”
Section: Introductionmentioning
confidence: 99%
“…The use of even lightweight graduated compression hosiery has been shown to improve venous symptoms of discomfort, swelling, fatigue, aching and leg tightness. 1 For many, all that is required is simple reassurance that the risk of future complications is low.…”
mentioning
confidence: 99%